Pengaruh Mobilisasi Dini terhadap Perubahan Tanda-tanda Vital pada Pasien Infark Miokard Akut - Akhmad Rifai; Suharyo Hadisaputro; Supriyadi Supriyadi (Jurnal LINK, 2015)
The aim of this research is to prove the influence of early mobilization on the changes of vital signs in patients with acute Myocard infraction. This study uses True Experimental reseach design with Randomized Pre-Post-test Control Group Design. The sample of this study is IMA 90 patients who had normal haemodynamic. 45 respondents who are provided with early mobilization is classified as the intervention group and 45 respondents who are randomly selected as a control group. The data are analyzed using univariate frequency distribution table, while the bivariate data using paired t-test, Wilcoxon, and independent samples t-test. The result is: early mobilization influence the change in vital signs. In the pairs of group the p-value 0,01 by systolic blood pressure, 0,01 diastolic blood pressure, 0.01, pulse, 0,01 respiration and 0,01 by temperature, where as the unpaired group after treatment p-value of systolic blood pressure with 0.04, diastolic blood pressure 0.08, pulse 0,01, respiration 0,05 and 0,01 of temperatur. In conclusion, vital signs remained normal with early mobilization for patients with normal haemodinamic, eventhough there is a difference between pre-test and post-test result.